2022
DOI: 10.21037/qims-21-499
|View full text |Cite
|
Sign up to set email alerts
|

Histogram peritumoral enhanced features on MRI arterial phase with extracellular contrast agent can improve prediction of microvascular invasion of hepatocellular carcinoma

Abstract: Background: Preoperative microvascular invasion (MVI) prediction plays an important role in therapeutic decision-making of hepatocellular carcinoma (HCC). This study aimed to investigate the value of histogram based on the arterial phase (AP) of magnetic resonance imaging (MRI) with extracellular contrast agent compared with radiological features for predicting MVI of solitary HCC. Methods: In total, 113 patients with pathologically proven solitary HCC were retrospectively enrolled who received surgical resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Many previous studies on peritumoral characteristics of HCC were based on a single sequence [16,31]. For instance, Wang et al [31] accurately predicted the status of MVI using peritumoral histogram features based on AP images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies on peritumoral characteristics of HCC were based on a single sequence [16,31]. For instance, Wang et al [31] accurately predicted the status of MVI using peritumoral histogram features based on AP images.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies on peritumoral characteristics of HCC were based on a single sequence [16,31]. For instance, Wang et al [31] accurately predicted the status of MVI using peritumoral histogram features based on AP images. Recently, Yu et al [17] developed a hepatobiliary phase image-based radiomics model to predict the vessels encapsulating tumor clusters in HCC, and the peritumoral radiomics model outperformed the intratumoral radiomics model alone.…”
Section: Discussionmentioning
confidence: 99%
“…Their combined model showed good performance (AUC = 0.926) in predicting MVI when using data derived from all phases [ 75 ]. Another study [ 76 ] reported encouraging results from analysis of the histogram of the peritumoral region in post-contrast arterial phase MRI images to predict MVI in patients with single HCC lesions. On the contrary, Dai et al [ 77 ] concluded that a CNN model created using radiomic features derived from the hepatobiliary phase of enhanced MRI images using a gradient boosting decision tree (GBDT) classifier had the highest predictive accuracy regarding MVI.…”
Section: Managment Of Hccmentioning
confidence: 99%
“…By using radiomics to analyze peritumoral tissue, it is possible to predict Ki-67 expression in tumors ( 17 ). And in HCC, peritumoral tissue was thought to be associated with MVI and invasiveness ( 18 , 19 ).However, few studies have evaluated the relationship between peritumoral tissues and Ki-67 expression in HCC patients.…”
Section: Introductionmentioning
confidence: 99%